2016
DOI: 10.1007/978-3-319-24298-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Hamilton cycles in random graphs and hypergraphs

Abstract: Let H be an edge colored hypergraph. We say that H contains a rainbow copy of a hypergraph S if it contains an isomorphic copy of S with all edges of distinct colors.We consider the following setting. A randomly edge colored random hypergraph H ∼ H k c (n, p) is obtained by adding each k-subset of [n] with probability p, and assigning it a color from [c] uniformly, independently at random.As a first result we show that a typical H ∼ H 2 c (n, p) (that is, a random edge colored graph) contains a rainbow Hamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…This was improved to (1 + o(1))n log n random edges and (1 + o(1))n colors by Frieze and Loh [9]. This was sharpened still further by Ferber and Krivelevich [7] who showed that the number of edges can be reduced to the exact threshold for Hamiltonicity. Bal and Frieze considered the case where exactly n colors are available and showed that O(n log n) random edges are sufficient to obtain a rainbow Hamilton cycle.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This was improved to (1 + o(1))n log n random edges and (1 + o(1))n colors by Frieze and Loh [9]. This was sharpened still further by Ferber and Krivelevich [7] who showed that the number of edges can be reduced to the exact threshold for Hamiltonicity. Bal and Frieze considered the case where exactly n colors are available and showed that O(n log n) random edges are sufficient to obtain a rainbow Hamilton cycle.…”
Section: Introductionmentioning
confidence: 96%
“…We also prove a hitting time result for a related notion of Π-connected.The next phase of this study, concerns Hamilton cycles in random k-uniform hypergraphs. There are various notions of Hamilton cycle in this context, and Ferber and Krivelevich [7] proved that if m H edges are needed for a given type of hamilton cycle to exist w.h.p. then O(m H ) random edges and (1 + ǫ)m H colors are sufficient for a rainbow Hamilton cycles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A Hamilton cycle is called rainbow if no color appears twice on its edges. It was shown by Frieze and Loh and by Ferber and Krivelevich that for m(1+o(1))(logn+loglogn)n, if we color G(n,m) randomly with (1+o(1))n colors, then G(n,m) contains a rainbow‐Hamilton cycle. This implies that if we randomly [(1+o(1))n] color a typical graph of minimum degree δn, then w.h.p.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first important insights concerning Hamilton cycles in random digraphs, due to McDiarmid , is that one can use coupling arguments to compare certain probabilities between Dfalse(n,pfalse) and the random undirected graph Gfalse(n,pfalse) (see for more recent applications of McDiarmid's idea). In particular, using the known optimal results for Gfalse(n,pfalse), McDiarmid's work implies that if pfalse(logn+loglogn+ωfalse(1false)false)/n then Dfalse(n,pfalse) a.a.s .…”
Section: Introductionmentioning
confidence: 99%